Identification and analysis of two lebocins in the oriental armyworm Mythimna separata. (March 2021) - Liu, Fang-Fang; Ding, Chen; Yang, Li-Ling; Li, Hao; Rao, Xiang-Jun
Abstract: The insect immune system can produce defensive molecules, such as antimicrobial peptides (AMPs), to eliminate invading pathogens. Here, we report the identification of two cDNAs ( MseLeb1, MseLeb2 ) that encode lepidopteral lebocin preproproteins in the oriental armyworm, Mythimna separata . Their open reading frames are 483/492 bp that encode 161/164 aa peptides. MseLeb1 is mainly expressed in the fat body and epidermis, while MseLeb2 is mainly expressed in the fat body, Malpighian tube, and epidermis. They were significantly induced by Escherichia coli, Staphylococcus aureus, and Beauveria bassiana in hemocytes . The preproproteins can be processed after RXXR motifs into mature peptides. Multiple sequence alignment indicates that MseLeb1 (18–42, 121–161) are potentially active peptides. Five peptides were synthesized for analyses: 18–42, 121–161, 121–154, 121–151, 121–146. Synthetic peptides showed agglutinating activity, but no hemolytic activity. Bacterial growth assay, colony formation assay, and electron microscopy revealed that synthetic peptides can inhibit bacterial growth and disrupt bacterial cell wall. B. bassiana conidia and blastospores were lysed by synthetic peptides. These results indicate that MseLeb1 and MseLeb2 are immune responsive lebocins, and the mature peptides have antibacterial and antifungal activities. Highlights: Two cDNAs encoding lebocin preproproteins were identified from Mythimna separata . Transcripts were induced in hemocytes by E. coli, S. aureus and B. bassiana . Synthetic peptides show agglutinating, antibacterial, and antifungal activity.